DFT study of gases adsorption on sharp tip nano-catalysts surface for green fertilizer synthesis - Yahya, N. (American Institute of Physics Inc., 2016)
The energy minimization and spin modifications of sorbates with sorbents in magnetic induction method (MIM) play a vital role in yield of fertilizer. Hence, in this article the focus of study is the interaction of sorbates/reactants (H2, N2 and CO2) in term of average total adsorption energies, average isosteric heats of adsorption energies, magnetic moments, band gaps energies and spin modifications over identical cone tips nanocatalyst (sorbents) of Fe2O3, Fe3O4 (magnetic), CuO and Al2O3 (non-magnetic) for green nano-fertilizer synthesis. Study of adsorption energy, band structures and density of states of reactants with sorbents are purely classical and quantum mechanical based concepts that are vividly illustrated and supported by ADSORPTION LOCATOR and Cambridge Seriel Total Energy Package (CASTEP) modules following classical and first principle DFT simulation study respectively. Maximum values of total average energies, total average adsorption energies and average adsorption energies of H2, N2 and CO2 molecules are reported as -14.688 kcal/mol, -13.444 kcal/mol, -3.130 kcal/mol, - kcal/mol and -6.348 kcal/mol over Al2O3 cone tips respectively and minimum over magnetic cone tips. Whereas, the maximum and average minimum values of average isosteric heats of adsorption energies of H2, N2 and CO2 molecules are figured out to be 3.081 kcal/mol, 4.842 kcal/mol and 6.848 kcal/mol, 0.988 kcal/mol, 1.554 kcal/mol and 2.236 kcal/mol over aluminum oxide and Fe3O4 cone tips respectively. In addition to the adsorption of reactants over identical cone sorbents the maximum and minimum values of net spin, electrons and number of bands for magnetite and aluminum oxide cone structures are attributed to 82 and zero, 260 and 196, 206 and 118 for Fe3O4 and Al2O3 cones respectively. Maximum and least observed values of band gap energies are figured out to be 0.188 eV and 0.018 eV with Al2O3 and Fe3O4 cone structures respectively. Ultimately, with the adsorption of reactants an identical increment of 14 electrons each in up and down spins is resulted. Â© 2016 Author(s).